Liminality and learning: international placements as a rite of passage - Parker, Jonathan; Ashencaen Crabtree, Sara; Baba, Ismail; Carlu, Dolly Paul; Azman, Azlinda (Taylor & Francis Group, 2012)
This article reports findings from a collaborative study of UK student learning in Malaysia. We analyze the concept of liminality as a means of understanding the transitional process between states and statuses that social work students experience in practice learning. Here, in specific reference to immersion in new cultural contexts represented by international placements, the development and learning of students are explored in relation to the overlapping domains of familiar and unfamiliar ‘cultures’ and disciplinary practice. These findings carry implications in terms of the increasing popularity of international placements and the potential imposition of hegemonies of values and knowledge.